2017
DOI: 10.4149/av_2017_02_07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transcriptional profiles of interferons, CXCL10 and RIG-1 in influenza infected A549 cells stimulated with exogenous interferons

Abstract: Type I and type III interferons (IFNs) are induced by viral infection. It was concluded that these IFN species are identical in regulation and biological functions. However, these two systems differ in the tissue expression of their receptors and their transcriptional regulation is fundamentally different as well as cellular signaling pathways that drive expression of each IFN. Here, we have investigated the transcriptional profile of endogenous IFNs after stimulation of cells with exogenous IFNs and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Although with less activity than IFN-β1a, IFN-λ1, or IFN-λ2, IFN-ω appears to be more efficient at reducing viral titers than IFN-α2 [159]. A study from Lachova et al [160] showed that treatment of influenza-infected A549 cells with IFN-α and IFN-ω induces a similar amount of IFN-α, IFN-β and IFN-λ mRNA but differs in induction of CXCL10 and RIG-1 mRNA. In addition to IFN-ω, IFN-τ has biological effects against influenza virus.…”
Section: Influenza Virusmentioning
confidence: 99%
“…Although with less activity than IFN-β1a, IFN-λ1, or IFN-λ2, IFN-ω appears to be more efficient at reducing viral titers than IFN-α2 [159]. A study from Lachova et al [160] showed that treatment of influenza-infected A549 cells with IFN-α and IFN-ω induces a similar amount of IFN-α, IFN-β and IFN-λ mRNA but differs in induction of CXCL10 and RIG-1 mRNA. In addition to IFN-ω, IFN-τ has biological effects against influenza virus.…”
Section: Influenza Virusmentioning
confidence: 99%
“…Numerous studies have shown that IFN-λ, being a nonspecific activator of a large group of ISGs, exhibits antiviral activity against a whole group of negative strand ssRNA viruses: IVA [18,21,[33][34][35][36][37][38]; IBV [39]; RSV [2,40,41]; and LCMV [42]. Some positive strand ssRNA viruses are also affected, such as: HCV [14,[43][44][45]; Dengue virus [46,47]; and rhinovirus [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The approximately 13 kb genome encodes up to 18 proteins. An important host innate immune mechanism is the production of interferons (IFNs), which can establish an antiviral state by up-regulating interferon stimulated genes that interfere with various steps in the virus life cycle (Švančarová et al, 2015a,b;Škorvanová et al, 2015;Lachová et al, 2017). The neutralizing antibody is considered to be the main immune mechanism against influenza virus.…”
Section: T Cells and Influenza A Virus (Iav)mentioning
confidence: 99%
“…It has recently been shown, that increased pathogenicity of NS1-truncated virus (NS80) does not influence Th1/Th2 balance (Turianová et al, 2020). Th2 cytokines such as IL-4, IL-5, IL-6, IL-10 and IL-13, are associated with the development of the influenza virus encephalopathy and increased pathology (Betáková et al, 2017). Lethal influenza virus infection induces cytokine profiles corresponding to the mixed Th1/Th2 response in mice (Turianová et al, 2019).…”
Section: T Cells and Influenza A Virus (Iav)mentioning
confidence: 99%